Hesperetin relieves cisplatin-induced acute kidney injury by mitigating oxidative stress, inflammation and apoptosis. (1st August 2019) - Chen, Xinliang; Wei, Wei; Li, Yazhen; Huang, Jingbo; Ci, Xinxin
Abstract: Although cisplatin is an effective anticancer drug, its clinical application is limited due to various side effects, especially nephrotoxicity. In this study, we investigated the protective effects and possible mechanisms of hesperetin on cisplatin-induced kidney damage. In vitro, hesperetin significantly attenuated oxidative stress-induced apoptosis by reducing ROS levels in cisplatin-treated HK-2 cells. Simultaneously, hesperetin activated the Nrf2 signaling pathway and regulated its downstream genes, including NQO1 and HO-1. In vivo, hesperetin could significantly attenuate cisplatin-induced nephrotoxicity, blood urea nitrogen (BUN) and serum creatinine (SCr). Furthermore, hesperetin clarifies cisplatin-induced oxidative stress by reducing MDA/MPO levels and increasing SOD/GSH levels. In addition, from the histopathological analysis of the kidney, hesperetin significantly reduced the nephrotoxicity caused by cisplatin compared with the cisplatin group. Moreover, western blotting of renal tissue revealed that hesperetin activates Nrf2 in a dose-dependent manner, attenuates the MAPK signaling pathway against inflammation, and inhibits the expression of apoptotic proteins to protect kidneys from AKI caused by cisplatin. Altogether, these findings suggest that hesperetin may be a potential protectant against cisplatin-induced nephrotoxicity. Highlights: In vitro, hesperetin significantly attenuated oxidative stress-induced apoptosis. In vivo, hesperetin protects against cisplatin-induced AKI. The mechanisms involved Nrf2, anti-inflammatory and anti-apoptosis pathway.